2012
DOI: 10.4103/0970-9290.100460
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a combination of oral midazolam and low-dose ketamine on anxiety, pain, swelling, and comfort during and after surgical extractions of mandibular third molars

Abstract: Premedication with midazolam plus low-dose ketamine prior to surgical extraction of third molars can provide the patient with a comfortable procedure and good postoperative analgesia, with less swelling and significantly less pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 0 publications
0
14
1
1
Order By: Relevance
“…Contrary to these studies [32,34,36]; in our study comparison of facial measurements and mouth opening in both the groups showed overall no statistically significant difference on the 1st, 3rd and 7th post-operative days. Thus sub-mucosal infiltration of 0.5 mg/kg ketamine did not seem to be effective in reducing postoperative swelling or trismus.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…Contrary to these studies [32,34,36]; in our study comparison of facial measurements and mouth opening in both the groups showed overall no statistically significant difference on the 1st, 3rd and 7th post-operative days. Thus sub-mucosal infiltration of 0.5 mg/kg ketamine did not seem to be effective in reducing postoperative swelling or trismus.…”
Section: Discussioncontrasting
confidence: 99%
“…In various studies done by Satilmiş et al [32], Garip et al [33], Gupta et al [36] ketamine has shown to reduce postoperative pain and swelling in patients undergoing surgical removal of third molars and also provide a comfortable procedure for the surgeon and patient. But in contrast Lebrun et al [35] concluded that there was no benefit to pre-emptive administration of ketamine 300 lg/ kg iv whether administered pre-or postoperatively after assessing the effect on 84 patients scheduled for third molar surgical removal.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations